Design and Development of a Novel Invasive Blood Pressure Simulator for Patient's Monitor Testing - Bibbo, Daniele; Kijonka, Jan; Kudrna, Petr; Penhaker, Marek; Vavra, Petr; Zonca, Pavel (Sensors, 2020)
This paper presents a newly-designed and realized Invasive Blood Pressure (IBP) device for the simulation on patient's monitors. This device shows improvements and presents extended features with respect to a first prototype presented by the authors and similar systems available in the state-of-the-art. A peculiarity of the presented device is that all implemented features can be customized from the developer and from the point of view of the end user. The realized device has been tested, and its performances in terms of accuracy and of the back-loop measurement of the output for the blood pressure regulation utilization have been described. In particular, an accuracy of ±1 mmHg at 25 °C, on a range from -30 to 300 mmHg, was evaluated under different test conditions. The designed device is an ideal tool for testing IBP modules, for zero setting, and for calibrations. The implemented extended features, like the generation of custom waveforms and the Universal Serial Bus (USB) connectivity, allow use of this device in a wide range of applications, from research to equipment maintenance in clinical environments to educational purposes. Moreover, the presented device represents an innovation, both in terms of technology and methodologies: It allows quick and efficient tests to verify the proper functioning of IBP module of patients' monitors. With this innovative device, tests can be performed directly in the field and faster procedures can be implemented by the clinical maintenance personnel. This device is an open source project and all materials, hardware, and software are fully available for interested developers or researchers.
Keywords: Blood Pressure; Blood Pressure Determination; monitorování fyziologických funkcí; monitory krevního tlaku; software; lidé; krevní tlak; Monitoring, Physiologic; Calibration; Software; měření krevního tlaku; Humans; Blood Pressure Monitors; kalibrace; Equipment Design; design vybavení